SURGICAL TREATMENT OF HEMORRHOIDAL BLEEDING IN PATIENTS WITH CARDIOVASCULAR DISEASES UNDER ANTICOAGULANT AND ANTIPLATELET THERAPY - A. Z. Tsitskarava; A. U. Korolkov; G. G. Hubulava; A. N. Demin (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to build an algorithm for medical and surgical treatment of hemorrhoidal bleedings in patients with cardiovascular diseases under anticoagulant and antiplatelet therapy.MATERIAL AND METHODS. The research was based on the analysis of results of treatment of hemorrhoidal bleedings in 86 patients with comorbidity (chronic combined hemorrhoids (2–4 stages) and cardiovascular diseases) under antiplatelet and antithrombotic therapy. Doppler-guided hemorrhoid artery ligation (with or without recto-anal repair) was used for the patients from the study group with no interrupting regular antiplatelet and anticoagulant therapy, whereas, in control group of patients, antithrombotic therapy was rejected for three to seven days in order to implementation of hemorrhoidectomy by Milligan – Morgan.RESULTS. The doppler-guided hemorrhoid artery ligation with recto-anal repair was a minimally invasive method without intra-operative blood loss with lowest pain syndrome at the short in hospital staying in comparison to hemorrhoidectomy by Milligan – Morgan. This fact determined the great clinical and economic effectiveness of the research method for the treatment of hemorrhoidal bleedings in patients with comorbidity.CONCLUSION. The minimal invasive surgical method of treatment hemorrhoidal bleedings – doppler-guided hemorrhoid artery ligation – could be used for patients with cardiovascular diseases and did not require interrupting anticoagulant and antiplatelet therapy.The authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.